2010
DOI: 10.1016/j.jmb.2010.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Key Amino Acid Residues Involved in Multi-Point Binding Interactions between Brazzein, a Sweet Protein, and the T1R2–T1R3 Human Sweet Receptor

Abstract: The sweet protein brazzein activates the human sweet receptor, a heterodimeric G-protein coupled receptor (GPCR) composed of subunits T1R2 and T1R3. In order to elucidate the key amino acid(s) responsible for this interaction, we mutated residues in brazzein and each of the two subunits of the receptor. The effects of brazzein mutations were assayed by a human taste panel and by an in vitro assay involving receptor subunits expressed recombinantly in human embryonic kidney cells; the effects of the receptor mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 50 publications
6
106
0
Order By: Relevance
“…Subsequently, Koizumi et al (2007), using human/mouse chimeric constructs expressed in HEK cells and intracellular calcium mobilization assays, have demonstrated that the protein neoculin, which tastes sweet to man but not mice, is indeed received by the Nterminal domain of T1R3. However, the wedge model has now been found not to be consistent with the results of mutational analysis, at least in the case of brazzein (Assadi- Porter et al, 2010). On the other hand, Jiang et al (2004), also by using human/mouse chimeras and by performing site-directed mutagenesis experiments, came to the conclusion that the cysteine-rich region of human T1R3 determines the responses to intensely sweet proteins such as brazzein or monellin and might be part of their binding site (Fig.…”
Section: Allosteric Modulation Of Family C Gpcrsmentioning
confidence: 93%
“…Subsequently, Koizumi et al (2007), using human/mouse chimeric constructs expressed in HEK cells and intracellular calcium mobilization assays, have demonstrated that the protein neoculin, which tastes sweet to man but not mice, is indeed received by the Nterminal domain of T1R3. However, the wedge model has now been found not to be consistent with the results of mutational analysis, at least in the case of brazzein (Assadi- Porter et al, 2010). On the other hand, Jiang et al (2004), also by using human/mouse chimeras and by performing site-directed mutagenesis experiments, came to the conclusion that the cysteine-rich region of human T1R3 determines the responses to intensely sweet proteins such as brazzein or monellin and might be part of their binding site (Fig.…”
Section: Allosteric Modulation Of Family C Gpcrsmentioning
confidence: 93%
“…There are also structural and sequential variations of the sweet taste receptor in various species (44) . Recent investigations demonstrate different functional roles of the subunits as well as the presence of discrete sites responsible for binding ligands of different chemical structures (45) . In lingual epithelium, the key elements of taste transduction pathways are a-, b-and g-subunits of gustducin, phospholipase Cb2 and transient receptor potential melastatin 5, a Ca 2 + -activated cation channel (46)(47)(48) .…”
Section: Sweet Taste Receptor Of Lingual Epitheliummentioning
confidence: 99%
“…The present work studied the hydrophobicity through carbon content on a number of brazzein mutants previously reported with focus on the two critical regions of the molecule suggested to be responsible for its sweetness [1,8,9,15]. As revealed in the results, the two regions with residues 29-33 and 39-43 including residue 36 between these segments, exists a remarkable variation between brazzein mutants with the increased sweetness taste mainly at residues 29, 31 and 41 and mutants with reduced sweetness taste at residues 30, 33, 36 and 43.…”
Section: Discussionmentioning
confidence: 99%
“…Brazzein mutants used in this study are based on mutagenesis studies in brazzein's two important regions previously reported as determinants of sweetness taste of the protein at residues 29-33 and 39-43, plus residue 36 [1,8,9]. The residues specifically examined were in position number 29, 30, 31, 33, 36, 41 and 43.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation